Anger in selected psychotherapeutical approaches - Czuma, Iwona; Cwalina, Ewa (Studia Psychologica: Theoria et praxis, 2012)
The purpose of this paper is to discuss the problem of anger in the context of selectedpsychotherapeutical approaches. Anger is a primarily adaptive emotion, indispensableto the correct functioning of a human being, providing protection and security, as well asregulating interpersonal contacts. However, it can become an unadapted emotion throughassociation with previous traumatic experiences, thus making a healthy reaction moredifficult. It is unadapted anger that often becomes the focus of psychotherapeutic work.Many approaches to unadapted anger and the multitude of aspects of this phenomenonallow to better understand a person who reacts with anger to events affecting them. Theyalso enable the therapist to select the most adequate form of help.